Membrane microdomains, rafts, and detergent-resistant membranes in plants and fungi - Malinsky, Jan; Großmann, Guido (Annual review of plant biology, 2013)
The existence of specialized microdomains in plasma membranes, postulated for almost 25 years, has been popularized by the concept of lipid or membrane rafts. The idea that detergent-resistant membranes are equivalent to lipid rafts, which was generally abandoned after a decade of vigorous data accumulation, contributed to intense discussions about the validity of the raft concept. The existence of membrane microdomains, meanwhile, has been verified by unequivocal independent evidence. This review summarizes the current state of research in plants and fungi with respect to common aspects of both kingdoms. In these organisms, principally immobile microdomains large enough for microscopic detection have been visualized. These microdomains are found in the context of cell-cell interactions (plant symbionts and pathogens), membrane transport, stress, and polarized growth, and the data corroborate at least three mechanisms of formation. As documented in this review, modern methods of visualization of lateral m...
Gesehen am 19.05.2017